2011
DOI: 10.1111/j.1365-2826.2011.02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Non-Canonical Notch Ligand Delta-Like Protein 1 in Hormone-Producing Cells of the Adult Male Mouse Pituitary

Abstract: To better understand the role of the non-canonical Notch ligand delta-like protein 1 (DLK1), in hormone-producing cells, we studied the cell distribution and subcellular localisation of DLK1 in the pituitary of male adult 129/SvJ mice, and analysed the variations in the hormone-producing cells associated with the lack of this gene in Dlk1 knockout mice. The results obtained showed the presence of DLK1-immunoreactive (ir) cells in all hormone-producing cells of the anterior pituitary. Immunoelectron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 45 publications
(59 reference statements)
8
40
1
Order By: Relevance
“…e observed expression pattern of DLK1 in the developing pituitary implies that DLK1 is also involved in regulating the differentiation of pituitary cell types, probably by modulating Notch signalling activity. In agreement, adult pituitary of Dlk1 knockout mice showed decreased numbers of growthhormone immunoreactive cells and reduced follicle stimulating hormone (FSH) and prolactin immunoreactivity [36].…”
Section: Dlk1 and Notch During Pituitary Gland Developmentsupporting
confidence: 51%
“…e observed expression pattern of DLK1 in the developing pituitary implies that DLK1 is also involved in regulating the differentiation of pituitary cell types, probably by modulating Notch signalling activity. In agreement, adult pituitary of Dlk1 knockout mice showed decreased numbers of growthhormone immunoreactive cells and reduced follicle stimulating hormone (FSH) and prolactin immunoreactivity [36].…”
Section: Dlk1 and Notch During Pituitary Gland Developmentsupporting
confidence: 51%
“…Several previous studies have implicated DLK1 in GH regulation (38)(39)(40)(41), and also conversely GH in the regulation of DLK1 (42)(43)(44). Notably, a recent study reported a reduction in GH secretion after Dlk1 deletion (40).…”
Section: Discussionmentioning
confidence: 96%
“…Mouse macrophages express Dlk1 moderately as compared with other cell types [32][33][34]. However, human monocytes, and the human monocytic cell line U937, express higher levels of DLK1 that diminish after their differentiation to macrophages, whereas, in general, the expression of NOTCH receptors increases in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our previous work revealed that Dlk1-deficient mice showed an increased primary T-dependent antibody response [31]. These results are consistent with an improved antigen presentation by macrophages and dendritic cells from Dlk1-null animals, which can be due, at least in part, to a greater expression of co-stimulatory molecules and cytokines implicated in T-cell differentiation.Mouse macrophages express Dlk1 moderately as compared with other cell types [32][33][34]. However, human monocytes, and the human monocytic cell line U937, express higher levels of DLK1 that diminish after their differentiation to macrophages, whereas, in general, the expression of NOTCH receptors increases in this process.…”
mentioning
confidence: 99%